Consensual Fictions : Women, Liberalism, and the English Novel. - Jones, Wendy S. (University of Toronto Press, 2004)
In Consensual Fictions, Wendy S. Jones focuses on the English novel of the period to explore the relationship between married love, classic liberal thought, and novelistic form.